Turkish validity and reliability study of the falsified hand sanitizer identification scale - Karaçorlu, Fatma Nur; Pirincci, Edibe (My University, 2024)
Background: The objective of this study was to assess the validity and reliability of the Falsified Hand Sanitizer Identification Scale in Turkish culture and language, which was developed to help consumers identify safe and effective hand disinfectants. Methods: Between February and April 2021, this methodological study used an online questionnaire to survey state university staff members. 355 people were reached. The scale’s Turkish validity was assessed using language (translationback translation), construct (confirmatory factor analysis (CFA)), and known group validity. Cronbach’s alpha internal consistency coefficient was used to assess reliability, as well as item-total correlation analysis and the test-retest method (Spearman correlation analysis). Results: The majority of the participants (62.18%, n = 217) were male. The mean age of all participants was 41.14 ± 9.80 years. In DFA, x2/sd = 3.67, with CFI = 0.98, GFI = 0.92, NFI = 0.97, and RMSEA = 0.08. As the frequency of daily use of sanitizer increased, the score obtained from the scale increased (p < 0.001). When all of the items were removed from the scale, its Cronbach’s alpha coefficient decreased. The Cronbach’s alpha coefficient for the scale was 0.934, with 0.892 for factor 1, 0.891 for factor 2, and 0.818 for factor 3. The corrected item-total correlation coefficients for all items ranged between 0.584 and 0.758. The test-retest correlation coefficient was 0.859 (p < 0.001). Conclusion: The Turkish Falsified Hand Sanitizer Identification Scale is a valid and reliable 5-point Likert scale consisting of 12 items and three sub-dimensions.
Keywords: COVID-19; Validity; Disinfectant; Reliability.